Pelanggaran Tindak Pidana Lalu Lintas yang di Lakukan oleh Seorang Warga Negara Asing (WNA) di Kawasan Badung Bali yang Mengakibatkan Hilangnya Nyawa Seseorang - Dewa Gede Dirgayusa Werdi Bumi; Anak Agung Sagung Laksmi Dewi; I Wayan Arthanaya (Jurnal Konstruksi Hukum, 2022)
Bali is a well-known tourist destination in the international world. In supporting their daily activities, not a few foreign tourists use vehicles individually. And not a few tourists who violate traffic. The occurrence of traffic violations on the highway tends to allow accidents. The purpose of this research is to discuss the regulation of the rights of foreign nationals who commit traffic violations that result in the loss of a person's life and to examine the criminal factors against foreign nationals who commit traffic violations resulting in the loss of a person's life. This research uses empirical legal research methods using a juridical and sociological approach. The sources of legal materials used in this research are primary, secondary and tertiary sources. Data collection techniques in this research used interview techniques and note-taking and documentation techniques. The results of this research explain that foreign nationals have rights as witnesses in a process of proving a criminal case which is regulated in the provisions of Article 26 paragraph (2) of the 1945 Constitution of the Republic of Indonesia which is specifically regulated regarding rights as citizens. Foreign. The lack of law enforcement against foreigners driving in the territory of Indonesia, especially Bali, is a factor causing accidents. It is hoped that the government will be able to tighten the enforcement of rules against foreigners driving in Indonesian territory and for rental parties to pay more attention to driving requirements for foreigners.